The dihydrofolate reductase 19-bp deletion modifies the beneficial effect of B-vitamin therapy in mild cognitive impairment: pooled study of two randomized placebo-controlled trials. Issue 7 (12th November 2021) - Wu, Yuanyuan; Smith, A David; Bastani, Nasser E; Refsum, Helga; Kwok, Timothy
Abstract: Background: Higher serum homocysteine is associated with cognitive decline in older people. But homocysteine-lowering trials including folic acid (FA) show inconsistent results on cognitive decline. The reduction of FA to dihydrofolate by dihydrofolate reductase (DHFR) is slow in humans. Objective: We examined the effects of the DHFR 19-bp deletion/insertion ( del/ins ) polymorphism on FA-containing treatment on cognitive decline and brain atrophy in older people with mild cognitive impairment (MCI). Methods: This study used pooled data from two randomized B-vitamin trials on 545 MCI subjects who received either FA-containing B vitamins or placebo for 24 months. Subjects were typed for the DHFR genotype. Primary outcome was the Clinical Dementia Rating scale-global score (CDR-global). Secondary outcomes were CDR-sum of boxes score (CDR-SOB), memory and executive Z -scores and whole brain atrophy rate by serial MRI. Results: The proportions of subjects with del/del, del/ins and ins/ins genotype were 29.5, 44.3 and 26.1%, respectively. DHFR genotypes modified the effects of B vitamins on CDR-global, CDR-SOB and executive function Z -score ( P interaction = 0.017, 0.014 and 0.052, respectively), with significant benefits being observed only in those with ins/ins genotype (Beta = −1.367, −0.614 and 0.315, P = 0.004, 0.014 and 0.012, respectively). The interaction was not significant for memory Z -score and whole brain atrophy rate. Notably, the supplements only slowed brain atrophy in members of the ' ins/ins ' group who were not using aspirin. Conclusions: Our data indicate that the beneficial effects of B vitamins including FA on cognitive function are only apparent in those with ins/ins genotype, i.e. relatively better preserved DHFR activity.